Correlation between the ease of cage plates implantation and endplate Hounsfield unit value during ACDF: a retrospective study - Guozheng Jiang; Luchun Xu; Yongdong Yang; Jianbin Guan; Yukun Ma; Ningning Feng; Ziye Qiu; Zeyu Li; Guanlong Wang; Jiaojiao Fan; Yi Qu; Xing Yu (BMC Surgery)
Abstract Objective To investigate the correlation between the implantation status of the ROI-C cervical cage plates and the Hounsfield unit(HU) value of the target vertebral endplate during anterior cervical decompression and fusion (ACDF)surgery. Methods Review of patient data undergoing ACDF from January 2018 to December 2021. Data on gender, age, body mass index, history of hypertension, diabetes, hyperlipidemia, smoking, alcohol consumption, cervical cage plates status, and HU values of the cervical vertebral endplate. Logistic regression analysis was used to evaluate the relationship between the HU values and the plates status. Results A total of 17 cases (12.1%) had misplaced implants during surgery. There were statistical differences in gender, long-term smoking history, drinking history, and cervical vertebral endplate HU values between the abnormal implantation group and the normal implantation group (P < 0.05). The cervical vertebral endplate HU values in the abnormal implantation group were significantly higher than those in the normal implantation group (729.3 ± 36.2 HU vs. 484.4 ± 59.2 HU, P < 0.001). In the logistic regression analysis, cervical endplate HU value (OR 1.081; 95% CI 1.016–1.375) was an independent factor influencing improper plate implantation. The area under the ROC curve (AUC) for the cervical endplate HU value in predicting implantation difficulty was 0.836 (P < 0.05), with an optimal threshold of 724 HU (sensitivity 83.2%; specificity 90.4%). Conclusions The cervical vertebral segment endplate HU value can independently predict whether the implantation of the plates is misplaced during ACDF surgery.